New Harmony, Indiana : Like a River, Not a Lake: A Memoir - McCaslin, Nancy Mangum; Owen, Jane Blaffer; Owen, Anne Blaffer (Book collections on Project MUSE., 2015)
For nearly seven decades, Jane Blaffer Owen was the driving force behind the restoration and revitalization of the town of New Harmony, Indiana. In this delightful memoir, Blaffer Owen describes the transformational effect the town had on her life. An oil heiress from Houston, she met and married Kenneth Dale Owen, great-great-grandson of Robert Owen, founder of a communal society in New Harmony. When she visited the then dilapidated town with her husband in 1941, it was love at first sight, and the story of her life and the life of the town became intertwined. Her engaging account of her journey to renew the town provides glimpses into New Harmony's past and all of its citizens--scientists, educators, and naturalists--whose influence spread far beyond the town limits. And there are fascinating stories of the artists, architects, and theologians who became part of Blaffer Owen's life at New Harmony, where, she says, "My roots could sink deeply and spread."